The Use of Electronic Health Records for Behavioral Phenotyping of School-Age Children With Unilateral Hearing Loss: A Methodological Approach. - Davis, Hilary; Leigh Anne Tang; Picou, Erin M.; Bastarache, Lisa; Tharpe, Anne Marie (Journal of Speech, Language & Hearing Research, 2024)
Purpose: This methodological study describes a technique for extracting information from de-identified electronic health records (EHRs) to identify occurrences of permanent unilateral hearing loss (UHL) and associated educational comorbidities. Method: This was an exploratory methodological study utilizing approximately 3.3 million de-identified medical records. Structured and unstructured data were extracted using both automated and manual methods. When both methods were available, positive and negative predictive values were calculated to evaluate the utility of using automated methods. Results: We defined a cohort of 471 records that met our criteria of school-age children with permanent UHL and no additional significant disabilities/diagnoses. Fifty-one percent of the children reflected in this cohort had indicators of adverse educational progress, defined as documentation of receiving educational services, speech-language therapy, and/or parental/teacher concern, with 12% of records reflecting overlapping services/concerns. Negative predictive values were generally high and positive predictive values were generally low, suggesting automated searches are useful for excluding factors of interest, but not finding them. Conclusions: This study demonstrates the feasibility of using EHRs in examining UHL in school-age children. By restricting our cohort to individuals who were seen in audiology clinic, we were able to capture variables such as educational difficulty that are not routinely ascertained in medical contexts. The proportion of children in this cohort demonstrating a marker of adverse educational progress is consistent with numerous prior observational studies, thus providing validity to this ascertainment approach. We describe challenges encountered in creating this cohort and detail our hybrid approach to ascertaining key variables accurately.